The effectiveness of play therapy on the aggressive behavior of children with ADHD - Panahian Amiri, Samaneh; Akbar Nataj, Kolsoum; Fakhri, Mohammadkazem (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of play therapy on the aggressive behavior of children with ADHD. Methods: The statistical population of this study includes all children with confrontational disobedience disorder in Babol in 2019, from which 60 people were purposefully selected and using a random method in two groups of play therapy and control group, each group was assigned 30 people. Data were obtained using a child behavioral problems questionnaire in three time periods: pre-test, post-test and follow-up. Play therapy was performed in ten sessions for 2 hours weekly for the experimental group. Analysis of variance with repeated measures and SPSS software were used to analyze the data. Results: The results showed that there was a significant difference between the effectiveness of play therapy on improving aggressive behavior (F=38.86, p<0.001) in children with ADHD. Conclusion: The study showed that play therapy reduced the aggressive behavior of children with ADHD and this treatment can be used to improve the aggressive behavior of children with ADHD.